A practical guide to the NEC3 professional services contract - Rowlinson, Michael (Hoboken : John Wiley & Sons, 2012)
Currently in its third edition, the NEC suite has become one of the UK's leading families of standard forms of contract for major construction and civil engineering projects. Part of the NEC suite, the Professional Services Contract (PSC) was drafted with the same process-based approach and objectives, offering a standard contract for the appointment of consultants providing professional services in an engineering or construction project. Embodying best practice in terms of project management, the basic philosophy of the PSC differs from the principles and approach of other standard cont.
Introduction -- Background to the NEC family of contracts -- The options : an overview -- 'Spirit of mutual trust and cooperation' -- The cast of characters -- Communications, early warnings and other general matters -- The parties' main responsibilities -- Subconsulting -- Quality -- Rights to material -- Indemnity, insurance and liability -- Time -- Payment -- Compensation events : theory and events -- Compensation events : procedures -- Compensation events : assessment -- Termination -- Dispute resolution -- Secondary options -- Completing the contract dataents -- The supporting documents : need and content.
Print version record.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: NEC Contracts; NEC Contracts; Civil engineering contracts -- Great Britain; Architectural contracts -- Great Britain; x; LAW -- Military; Architectural contracts; Civil engineering contracts; Great Britain